Enhanced extraction efficiency of miRNA from cells by addition of Triton X-100 - Ban, Eunmi; Chae, Dong-Kyu; Song, Eun Joo (SPRINGER HEIDELBERG, 2013)
The determination of microRNA (miRNA) levels in biomaterials has become important for understanding their biological functions and for the diagnosis of various diseases. An effective extraction method is needed for maximizing the recovery of miRNAs from cells, while minimizing RNA degradation during the extraction because miRNAs present only approximately 0.01 % of total RNA. In this study, we used Triton X-100 (TX-100) to improve the extraction efficiency of miRNAs with TRIzolA (R) reagent, which is a commonly used commercial microRNA isolation kit. The concentration of TX-100 and the incubation time after the addition of TX-100 were optimized to maximize the extraction efficiency. The extraction recovery by a combination of TX-100 and TRIzolA (R) reagent was approximately 1.9-fold greater than that by the TRIzolA (R) reagent alone. We have established a very effective extraction method for the extraction of low-abundance miRNAs in biological samples for the determination of miRNA levels in biomaterials.
Keywords: RNA ISOLATION; MICRORNAS; BIOGENESIS